Frailty in Nursing Home Residents - A Comparison of the FRAIL-NH and Clinical Frailty Scale - Großhauser, Franz; Schöne, Daniel; Kiesswetter, Eva; Sieber, Cornel; Volkert, Dorothee (ZEITSCHRIFT FUR GERONTOLOGIE UND GERIATRIE, 2022)
CRIS-Team WoS Importer:2022-09-16

Frailty in Nursing Homes—A Prospective Study Comparing the FRAIL-NH and the Clinical Frailty Scale - Großhauser, Franz; Schöne, Daniel; Kiesswetter, Eva; Sieber, Cornel; Volkert, Dorothee (Journal of the American Medical Directors Association, 2022)
Objectives: Frailty is common in nursing home (NH) residents, but its prevalence in German institutions is unknown. Valid and easy-to-use screening tools are needed to identify frail residents. We used the FRAIL-NH scale and the Clinical Frailty Scale (CFS) to (1) obtain the prevalence of frailty, (2) investigate the agreement between both instruments, and (3) evaluate their predictive validity for adverse health events in German NH residents. Design: Prospective cohort study. Setting and participants: German NH residents (n = 246, age 84 ± 8 years, 67% female). Methods: Frailty status was categorized according to FRAIL-NH (nonfrail, frail, most frail) and CFS (not frail, mild to moderately frail, severely frail). Agreement between instruments was examined by Spearman correlation, an area under the receiver operating characteristic curve (AUC) with 95% CI, and sensitivity and specificity using the “most frail” category of FRAIL-NH as reference standard. Adverse health events (death, hospital admissions, falls) were recorded for 12 months, and multivariate cox and logistic regression models calculated. Results: According to FRAIL-NH, 71.1% were most frail, 26.4% frail, and 2.5% nonfrail. According to CFS, 66.3% were severely frail, 26.8% mild to moderately frail, and 6.9% not frail. Both scales correlated significantly (r = 0.78; R2 = 60%). The AUC was 0.92 (95% CI 0.88-0.96). Using a CFS cutoff of 7 points, sensitivity was 0.90 and specificity 0.92. The frailest groups according to both instruments had an increased risk of death [FRAIL-NH hazard ratio (HR) 2.19, 95% CI 1.21-3.99; CFS HR 2.56, 95% CI 1.43-4.58] and hospital admission [FRAIL-NH odds ratio (OR) 1.95, 95% CI 1.06-3.58; CFS OR 1.79, 95% CI 1.01-3.20] compared to less frail residents. The FRAIL-NH predicted recurrent faller status (OR 2.57, 95% CI 1.23-5.39). Conclusions and implications: Frailty is highly prevalent in German NH residents. Both instruments show good agreement despite different approaches and are able to predict adverse health outcomes. Based on our findings and because of its simple administration, CFS may be an alternative to FRAIL-NH for assessing frailty in NHs.
CRIS-Team Scopus Importer:2022-10-14
Keywords: aged; Clinical Frailty Scale; Frail-NH scale; frailty; nursing homes

Management of Malnutrition in Older Patients-Current Approaches, Evidence and Open Questions - Volkert, Dorothee; Beck, Anne Marie; Cederholm, Tommy; Cereda, Emanuele; Cruz-Jentoft, Alfonso; Goisser, Sabine; De Groot, Lisette; Großhauser, Franz; Kiesswetter, Eva; Norman, Kristina; Pourhassan, Maryam; Reinders, Ilse; et al. (Journal of Clinical Medicine, 2019)
Malnutrition is widespread in older people and represents a major geriatric syndrome with multifactorial etiology and severe consequences for health outcomes and quality of life. The aim of the present paper is to describe current approaches and evidence regarding malnutrition treatment and to highlight relevant knowledge gaps that need to be addressed. Recently published guidelines of the European Society for Clinical Nutrition and Metabolism (ESPEN) provide a summary of the available evidence and highlight the wide range of different measures that can be taken-from the identification and elimination of potential causes to enteral and parenteral nutrition-depending on the patient's abilities and needs. However, more than half of the recommendations therein are based on expert consensus because of a lack of evidence, and only three are concern patient-centred outcomes. Future research should further clarify the etiology of malnutrition and identify the most relevant causes in order to prevent malnutrition. Based on limited and partly conflicting evidence and the limitations of existing studies, it remains unclear which interventions are most effective in which patient groups, and if specific situations, diseases or etiologies of malnutrition require specific approaches. Patient-relevant outcomes such as functionality and quality of life need more attention, and research methodology should be harmonised to allow for the comparability of studies.
CRIS-Team WoS Importer:2019-08-23

Predictors of incident malnutrition—a nutritionDay analysis in 11,923 nursing home residents - Torbahn, Gabriel; Sulz, Isabella; Großhauser, Franz; Hiesmayr, Michael; Kiesswetter, Eva; Schindler, Karin; Sieber, Cornel C.; Visser, Marjolein; Weber, Jasmin; Volkert, Dorothee (European Journal of Clinical Nutrition, 2021)
Background/Objectives Malnutrition (MN) in nursing home (NH) residents is associated with poor outcome. In order to identify those with a high risk of incident MN, the knowledge of predictors is crucial. Therefore, we investigated predictors of incident MN in older NH-residents. Subjects/Methods NH-residents participating in the nutritionDay-project (nD) between 2007 and 2018, aged ≥65 years, with complete data on nutritional status at nD and after 6 months and without MN at nD. The association of 17 variables (general characteristics (n = 3), function (n = 4), nutrition (n = 1), diseases (n = 5) and medication (n = 4)) with incident MN (weight loss ≥ 10% between nD and follow-up (FU) or BMI (kg/m2) < 20 at FU) was analyzed in univariate generalized estimated equation (GEE) models. Significant (p < 0.1) variables were selected for multivariate GEE-analyses. Effect estimates are presented as odds ratios and their respective 99.5%-confidence intervals. Results Of 11,923 non-malnourished residents, 10.5% developed MN at FU. No intake at lunch (OR 2.79 [1.56–4.98]), a quarter (2.15 [1.56–2.97]) or half of the meal eaten (1.72 [1.40–2.11]) (vs. three-quarter to complete intake), the lowest BMI-quartile (20.0–23.0) (1.86 [1.44–2.40]) (vs. highest (≥29.1)), being between the ages of 85 and 94 years (1.46 [1.05; 2.03]) (vs. the youngest age-group 65–74 years)), severe cognitive impairment (1.38 [1.04; 1.84]) (vs. none) and being immobile (1.28 [1.00–1.62]) (vs. mobile) predicted incident MN in the final model. Conclusion 10.5% of non-malnourished NH-residents develop MN within 6 months. Attention should be paid to high-risk groups, namely residents with poor meal intake, low BMI, severe cognitive impairment, immobility, and older age.

Reasons for and against nutritional interventions. An exploration in the nursing home setting - Großhauser, Franz; Kiesswetter, Eva; Torbahn, Gabriel; Sieber, Cornel; Volkert, Dorothee (Geriatrics, 2021)
Malnutrition (MN) is widespread in nursing homes. Sometimes, but not always, nutritional interventions (NIs) are made, and the reasons for or against NIs are unknown. The aim of this cross-sectional study was to describe these reasons for residents with and without MN according to nurses’ subjective judgement and according to objective signs of MN. The nutritional status of 246 nursing home residents was subjectively judged by nurses (MN, at risk of MN, no MN) and objectively assessed by body mass index (BMI), weight loss (WL), and low food intake. NIs (enriched meals and/or oral nutritional supplements) were recorded using a standardized questionnaire, and nurses’ main reasons for (not) giving NIs were obtained in an open question. Of the residents, 11.0% were subjectively malnourished, and 25.6% were at risk of MN; 32.9% were malnourished according to objective criteria. Overall, 29.7% of the residents received NIs, 70.4% of those with MN as assessed by the nurses, 53.0% of those with objective MN, and 11.0% and 18.0% of non-malnourished residents, respectively. Reasons for NIs most often stated were low intake (47.9%), WL (23.3%), and low BMI (13.7%). Reasons against NIs mostly mentioned were adequate BMI (32.9%) and sufficient intake (24.3%). The lack of NIs for residents with MN was partially—but not always—explained by valid reasons. As residents without MN frequently received NIs, criteria for both MN rating and providing NIs, require closer scrutiny.
CRIS-Team Scopus Importer:2021-10-08
Keywords: Aged; Awareness; Malnutrition; Nurse; Nursing home; Nutritional intervention